2020
DOI: 10.1038/s41598-020-73078-0
|View full text |Cite
|
Sign up to set email alerts
|

Chi hotspot control of RecBCD helicase-nuclease by long-range intramolecular signaling

Abstract: Repair of broken DNA by homologous recombination requires coordinated enzymatic reactions to prepare it for interaction with intact DNA. The multiple activities of enterobacterial RecBCD helicase-nuclease are coordinated by Chi recombination hotspots (5′ GCTGGTGG 3′) recognized during DNA unwinding. Chi is recognized in a tunnel in RecC but activates the RecB nuclease, > 25 Ǻ away. How the Chi-dependent signal travels this long distance has been unknown. We found a Chi hotspot-deficient mutant in the RecB h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Hence, when the two DNA binding sites in RecB and RecD are bound to ssDNA, the ADP nucleotide cofactor imposes a different degree of cooperativity, suggesting a different conformation and degree of interaction between RecB and RecD upon the different nucleotide cofactors. This may result from disrupting long-range intramolecular signaling between the three subunits as a response to different nucleotides ( 43 ).…”
Section: Resultsmentioning
confidence: 99%
“…Hence, when the two DNA binding sites in RecB and RecD are bound to ssDNA, the ADP nucleotide cofactor imposes a different degree of cooperativity, suggesting a different conformation and degree of interaction between RecB and RecD upon the different nucleotide cofactors. This may result from disrupting long-range intramolecular signaling between the three subunits as a response to different nucleotides ( 43 ).…”
Section: Resultsmentioning
confidence: 99%
“…Whilst the biochemical and in vivo activities of RecBCD have been extensively studied ([11, 16, 17, 18, 19], and [7, 20] for review), less is known about the regulation of its expression. RecBCD has been reported to be expressed at very low levels [21, 22] and is present in less than ten molecules per cell [23].…”
Section: Introductionmentioning
confidence: 99%
“…RecBCD then facilitates loading of RecA protein onto the resected 3' single strand resulting in a RecA filament that initiates homologous recombination. The RecB nuclease domain has been proposed to interact directly with RecA protein to facilitate its loading onto ssDNA [29].Since the proposed RecA binding site on the nuclease domain is occluded in the structures of RecBCD bound to DNA, it has been suggested that the nuclease domain is dynamic and may undock from the rest of RecBCD to facilitate RecA loading [29][30][31][32]. In fact, recent cryoEM structures of RecBCD bound to blunt-ended DNA show two classes of RecBCD-DNA structures [18].…”
mentioning
confidence: 99%
“…Since the proposed RecA binding site on the nuclease domain is occluded in the structures of RecBCD bound to DNA, it has been suggested that the nuclease domain is dynamic and may undock from the rest of RecBCD to facilitate RecA loading [29][30][31][32]. In fact, recent cryoEM structures of RecBCD bound to blunt-ended DNA show two classes of RecBCD-DNA structures [18].…”
mentioning
confidence: 99%